THE STURTIAN 'SNOWBALL' GLACIATION: FIRE AND ICE - Godderis Y.; Donnadieu Y.; Nedelec A.; Dupre B.; Dessert C.; Grard A.; Ramstein G.; Francois L.M. (My University, 2003)
The Sturtian 'snowball' glaciation (730 Ma) is contemporary with the dislocation of the Rodinia supercontinent. This dislocation is heralded and accompanied by intense magmatic events, including the onset of large basaltic provinces between 825 and 755 Ma. Among these magmatic events, the most important one is the onset of a Laurentian magmatic province at 780 Ma around a latitude of 30°N. The presence of these fresh basaltic provinces increases the weatherability of the continental surfaces, resulting in an enhanced consumption of atmospheric CO2 through weathering, inducing a global long-term climatic cooling. Based on recent weathering laws for basaltic lithology and on climatic model results, we show that the weathering of a 6x106 km2 basaltic province located within the equatorial region (where weathering of the province and consumption of CO2 are boosted by optimal climatic conditions) is sufficient to trigger a snowball glaciation, assuming a pre-perturbation PCO2 value of 280 ppmv. We show that the Laurentian magmatic province might be the main culprit for the initiation of the Sturtian 'snowball' glaciation, since the Laurentian magmatic province had drifted within the equatorial region by the time of the glaciation.
Keywords: SNOWBALL EARTH; GLACIATION; BASALTIC TRAPS; CARBON CYCLE; MODELING